The WHO Global Benchmarking Tool: a game changer for strengthening national regulatory capacity. Issue 8 (11th August 2020) - Guzman, Javier; O'Connell, Erin; Kikule, Kate; Hafner, Tamara
Abstract : Many low-income and middle-income countries lack the capacity to effectively and efficiently regulate medical products in their countries. To support countries in strengthening their capacity, WHO has developed the Global Benchmarking Tool (GBT) as the global standard for objectively assessing regulatory capacity for medicines and vaccines. The GBT is a game changer because it is the first globally accepted tool for assessing and strengthening national regulatory authorities. The inclusion of an institutional development plan in the GBT methodology provides context-specific actionable steps countries can take to advance their system's functionality and maturity. The GBT facilitates coordination and improves the effectiveness of regulatory strengthening efforts. The tool also facilitates regulatory reliance and harmonisation, which helps to improve timely access to quality-assured medicines, and creates incentives for trade, particularly in countries and regions with a strong pharmaceutical manufacturing base. The GBT is a necessary tool for creating strong and effective regulatory systems, which are critical for ensuring the efficacy, safety and quality assurance of medicines and populations' timely access to these medicines. In outlining the benefits of the GBT, this paper also offers some specific ideas for strengthening the GBT framework and process.